Charles-Louis De Secondat Montesquieu’s Activities and The Political Ethical Principles Serving Peace - Baxshilloyevich, Sharipov (Indonesian Journal Publisher, 2025)
This study explores the political and ethical principles of Charles-Louis de Secondat Montesquieu, focusing on his contributions to peace and governance. By analyzing Montesquieu’s works, particularly The Spirit of the Laws, the research highlights his advocacy for liberty, equality, and the separation of powers as essential elements of a stable and just government. The study employs a historical and philosophical approach to examine his influence on democratic thought and modern political structures. Montesquieu’s ideas emphasize that peace is achievable through just laws, balance in governance, and the moral responsibility of rulers and citizens. The findings suggest that his principles remain relevant in contemporary discussions on democracy and governance. Ultimately, the research concludes that Montesquieu’s ethical-political philosophy serves as a foundation for sustaining peace and stability in diverse political systems. This article examines the life and early peace ideas of Charles-Louis Montesquieu, a prominent representative of French national philosophy during the Renaissance, from the perspective of political ethics. The study highlights some of the most significant empirical conclusions of Montesquieu’s political philosophy, as identified by the author, and emphasizes the rational core of his political doctrine.